Temporal patterns in adult salmon migration timing across southeast Alaska. (6th February 2015) - Kovach, Ryan P.; Ellison, Stephen C.; Pyare, Sanjay; Tallmon, David A.
Abstract: Pacific salmon migration timing can drive population productivity, ecosystem dynamics, and human harvest. Nevertheless, little is known about long‐term variation in salmon migration timing for multiple species across broad regions. We used long‐term data for five Pacific salmon species throughout rapidly warming southeast Alaska to describe long‐term changes in salmon migration timing, interannual phenological synchrony, relationships between climatic variation and migratory timing, and to test whether long‐term changes in migration timing are related to glaciation in headwater streams. Temporal changes in the median date of salmon migration timing varied widely across species. Most sockeye populations are migrating later over time (11 of 14), but pink, chum, and especially coho populations are migrating earlier than they did historically (16 of 19 combined). Temporal trends in duration and interannual variation in migration timing were highly variable across species and populations. The greatest temporal shifts in the median date of migration timing were correlated with decreases in the duration of migration timing, suggestive of a loss of phenotypic variation due to natural selection. Pairwise interannual correlations in migration timing varied widely but were generally positive, providing evidence for weak region‐wide phenological synchrony. This synchrony is likely a function of climatic variation, as interannual variation in migration timing was related to climatic phenomenon operating at large‐ (Pacific decadal oscillation), moderate‐ (sea surface temperature), and local‐scales (precipitation). Surprisingly, the presence or the absence of glaciers within a watershed was unrelated to long‐term shifts in phenology. Overall, there was extensive heterogeneity in long‐term patterns of migration timing throughout this climatically and geographically complex region, highlighting that future climatic change will likely have widely divergent impacts on salmon migration timing. Although salmon phenological diversity will complicate future predictions of migration timing, this variation likely acts as a major contributor to population and ecosystem resiliency in southeast Alaska.